Exploring the electrical behavior of iodine substituted CaCu3Ti4O12-xIx by impedance and modulus spectroscopy - Yadav B.; Sinha P.; Kar K.K.; Ghorai M.K.; Kumar D. (My University, 2025)
This study explores the effect of iodine (an anion) substitution on the dielectric and resistive properties of CaCu3Ti4O12-xIx (x = 0, 0.005, 0.05, and 0.20) sintered at 1100 °C for 12 h with the help of impedance and modulus spectroscopy. The electrical measurements were done with varying temperatures (300–450 K) and frequency (20 Hz-1 MHz). The ionic distribution of different ions and iodine and their oxidation states were revealed by EDX and XPS analysis, supporting the synthesis of CCTO ceramics with iodine substitution. The complex plane plots (Z″ vs. Z′ and M″ vs. M′) and spectroscopic plots (Z″ vs. log f and M″ vs. log f) of various compositions at different temperatures suggest that the grains, grain boundaries, and sample-electrode interface contribute to their electrical response and can be represented by a combination of three R–C or R-CPE equivalent circuits. The depressed arcs in the Z″ vs. Z′ plot revealed multiple relaxations with a narrow distribution of time constants. The scaled master plots confirm that the resistive and polarization mechanisms are independent of temperature and are Maxwell-Wagner relaxations type. Broad relaxation peaks and mismatch in peak frequencies of Z″ and M″ vs. log f plots suggest that the relaxation mechanism is dominated by the short-range (localized) movement of charge carriers. The activation energies for grain and grain boundary relaxation processes are ∼0.15 eV and ∼0.2 eV, respectively. Increasing iodine doping from x = 0.005 to x = 0.05 leads to a large increase in the resistance of the specimen, which has been explained based on change of charge compensation for IO• defects from electronic defect e/ to ionic defects VCu// and/or VTi////. The dielectric constant is maximum for the composition, x = 0.2, whereas loss, tan δ is minimum for x = 0.05. © 2022 Elsevier Ltd